2002
DOI: 10.1038/nmat704
|View full text |Cite
|
Sign up to set email alerts
|

Highest electron affinity as a predictor of cluster anion structures

Abstract: Small clusters have a range of unique physical and chemical phenomena that are strongly size dependent. However, analysis of these phenomena often assumes that thermodynamic equilibrium conditions prevail. We compare experimentally measured and ab initio computed photoelectron spectra of bare and deuterated silicon cluster anions produced in a plasma environment. We find that the isomers detected experimentally are usually not the ground-state isomers, but metastable ones, which indicates that cluster relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 30 publications
7
53
0
Order By: Relevance
“…We note that the single-particle Kohn-Sham eigenvalues generated using popular DFT functionals are not expected to quantitatively agree with the IP and EA in practice, although in principle there is such a correspondence for the HOMO if the exact DFT functional is used. 45 The ΔSCF values are generally quite close to the G 0 W 0 values and can be used in order to shift DFT spectra for the purpose of comparison to photoelectron spectroscopy experiments, 46 as done below.…”
Section: Starting Point Sensitivitymentioning
confidence: 99%
“…We note that the single-particle Kohn-Sham eigenvalues generated using popular DFT functionals are not expected to quantitatively agree with the IP and EA in practice, although in principle there is such a correspondence for the HOMO if the exact DFT functional is used. 45 The ΔSCF values are generally quite close to the G 0 W 0 values and can be used in order to shift DFT spectra for the purpose of comparison to photoelectron spectroscopy experiments, 46 as done below.…”
Section: Starting Point Sensitivitymentioning
confidence: 99%
“…This combination of theory and experiment has been used successfully in the past to gain far-reaching physical insight, regarding e.g., the assignment of PES peaks to particular molecular orbitals, as exemplified by Refs. [1][2][3][4][5][6][7][8][9][10] Density functional theory (DFT) in the Kohn-Sham (KS) 11 or Generalized Kohn-Sham (GKS) 12 frameworks is currently the method of choice for electronic structure calculations for molecules and solids. When it comes to predicting electron removal energies however, the KS approach suffers from the fact that the interpretation of KS eigenvalues as electron removal energies is formally not based on solid ground.…”
mentioning
confidence: 99%
“…The VEA and VDE represent lower and upper bounds, respectively, of the electron affinity when the nuclear configuration is not significantly different in the anionic and neutral geometry. [30][31][32] Specifically, Mitsui et al 33 observed the formation of negatively-charged benzene clusters (C 6 H 6 ) − n . In the gas phase, the vertical detachment energy (VDE) is between 0.47 and 0.56 eV for n = 53 − 124 with an estimated value of 0.84 eV when n is extrapolated to infinity.…”
mentioning
confidence: 99%